From Reading to Dressing: Portraiture of a Qing Empress in Gender and Cross-Cultural Perspective - Lihui, Dong (Global Journal of Cultural Studies, 2022)
This paper argues that the abundance in quantity and innovation of the painted and photographic portraits commissioned by Empress Dowager Cixi between the latter years of the 19th and early years of the 20th centuries, exceeded that of any other late Qing emperor or royal consort, and it is the diversity of gender references presented among them that is particularly distinctive. Through separating such a practice of ritualised “gender performance” into three stages, from 1) the ‘masculinised’ pose of “reading” appearing frequently in works of an earlier period, through 2) the gender-neutral divine imagery of dressing as a bodhisattva, to 3) the late-period feminised image of “dressing in front of the mirror”, the purpose of this paper is to explore how gender is shown in a late Qing empress’ portraiture, which is subject to multifarious changes dependent on different domestic and international political demands. The conclusion is that 1) on the international stage as set in the early years of the 20th century, the image of a late Qing empress dowager participated in the broader shaping of China’s national image as something weak, feminine and disempowered, and 2) the essential incompatibility of Chinese and Western visual cultures was a major factor in the failures of the projection of the image of late Qing China overseas.